PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 010 SUNGAI PANJI-PANJI KECAMATANKUBU BABUSSALAM KABUPATENROKAN HILIR - Dianofita, Jemi; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is in art of the social, studies students learning outcomes with an average grade 58 while the value of minimum criteria of completeness (KKM) is 65. This research is classroom action research (CAR). Which aims to improve the social studies student learning outcomes at fourth grade of elementary school SDN 01 Sungai Panji-panji Kubu Rokan Hilir District. The data was colleted by using observation paper and bot the result by examination I and II. Thevalue of student learning out comes before CAR is average 58 with fair categori. Whereas after CAR in cycle I is everage 66,5% with fairly bood category and cycle II is average 70% in excellent category. So the improvement of students learning out comes from the bassed score to cycle I increase about 14,65% whereas from based score to cycle II increase about 20,68%. The activity of the teacher in first cycle with average 58,33% in bood category. Where the teacher activity in secord cycle is average 65,62% in good category the students activity in cycle I is about 45,83% in fairly good category whereas cycle II increase about 66,66%. The result of this research is the implementation of cooperative learning model type NHT can increase the social studies students learning outcomes at fourth brade of elementary school SDN 01 Sungai Panji-panji Kecamatan Kubu Rokan Hilir District.Key Word : Kooperative type Numbered Heads Together (NHT), The Social student achievement